Properties of particleboard from oil palm trunk in relation to resin content and wax addition / Mohammad Akhmal Sakiman - Sakiman, Mohammad Akhmal (Faculty of Applied Sciences, 2015)
In this study used oil palm trunk particle which obtained at Jengka plantation. Oil palm trunk is used as a raw material in the manufacture of particleboard. Currently there is many oil palm plantation on 2013 there is 5.23 million hectare of oil palm plantation which register on Malaysian Palm Oil Board. In this studied JIS(Japanese Industrial Standard).The objectives of the study is to determine the physical and mechanical properties particleboard made from oil palm trunk and to determine the effect of resin content (8%,10%, and 12%) and without wax addition (0%) and wax addition (1%) on particle board properties. The higher the resin content will produce a good particleboard, but in manufacturing to produce a high resin content particleboard will increase the cost. In this studied found that 10% resin content with wax addition is the best particleboard. That is because there is only minimal significance between 10% and 12% resin content.